ANALYSIS OF METHODS FOR PROCESSING SERA RAW MATERIALS AND PREPARATION OF SEROBETON - Akhmedov Islombek; Umarov Isroil; S.Kholmirzayev; F.Dadaxanov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. This scientific article analyzes the methods of disposal using the processing of Sera raw materials. The properties of Sera raw materials, its support as a binding material, the preparation of concrete and the comparison of cerobeton with Portland-based concrete were carried out. Also, in the field of zero betting, the possibilities for the production of serotonin using serotonin were analyzed.